Sources and intensity of access to agricultural information technologies by smallholder farmers: evidence from Northwest Ethiopia - Shitaye, Zebenay; Tadesse, Bamlaku; Enkuahone, Koyachew (Frontiers in Sustainable Food Systems, 2024)
Agriculture is a key sector in many African economies, making access to accurate agricultural information vital for boosting productivity. This study investigated the factors influencing smallholder farmers’ access to agricultural information in the East Gojjam zone of Amhara, Ethiopia. A cross-sectional survey of 403 households was conducted, and data were analyzed using Stata software with the Ordered Probit model. The study found that farmers’ access to agricultural information is significantly influenced by factors such as experience, exposure to electronic and printed media, farm size, access to extension services, input availability, market distance, proximity to development centers, and participation in Farmer Training Centers (FTC). Major constraints to information access included inadequate government policies, insufficient extension services, limited information sources, poor infrastructure, network issues, and a lack of effective knowledge exchange. The study recommends that smallholder farmers increase exposure to various media channels and participate in FTC programs. Additionally, the Ethiopian government should prioritize infrastructure improvements (mobile networks, roads, and electricity), expand extension services, and diversify information sources to improve farmers’ access to relevant agricultural knowledge. Addressing these barriers will help enhance agricultural productivity in the study area.